SOCIAL-ECONOMICAL SITUATION IN EASTERN COUNTRIES (American Journal of Interdisciplinary Research and Development, 2023)
The article analyzes the socio-economic situation in Eastern countries based on information from scientific literature and periodicals. Even after the Second World War, he tried hard to save this company. For this purpose, in 1949, Great Britain developed a treaty called "Supplementary Treaty". It provided for a partial increase in the amount of allocation to Iran from the company's income.